Kepatuhan Syari'ah Terhadap Keputusan Menjadi Anggota Koperasi Syari'ah Masjid Besar Baitul Amanah Kecamatan Ganeas - Neli Purwanti; Yopi Hidayatul Akbar (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2022)
The application of shari'ah compliance becomes very important because the system clearly uses shari'ah principles, so that the people in the district. Ganeas, especially people who are Muslim, can be more interested in becoming a member of the Syari'ah Cooperative, Baitul Amanah Grand Mosque, Kec. Ganeas because it can avoid harm. However, the fact is that until now there are still many doubts from the Kec. Ganeas to decide to become a member. The method used in this study is a quantitative method. The test and data analysis techniques include validity test, reliability test, percentage data description test, normality test, simple linear regression, Pearson correlation, t test and coefficient of determination (r2) using SPSS version 22. The sample in this study were all members of the Syari' Cooperative. ah Great Mosque of Baitul Amanah Kec. Ganeas is a number of 50 people.The results showed that the value of r2 was 0.268 which implies that the influence of the Shari'ah compliance variable (X) on the decision variable to become a member (Y) is 26.8% and the remaining 73.2% is influenced by other variables. The results of hypothesis testing using simple linear regression analysis show that sharia compliance has a significant effect on the decision to become a member. The conclusion of the research shows that the variable of Shari'ah compliance and the decision to become a member has a unidirectional relationship (b = 0.633), the level of closeness is moderate (r = 0.517), and the variable of Shari'ah compliance contributes to the variable of decision to become a member of 26.8%. with low criteria, then based on the results of hypothesis testing (t test), it shows that the hypothesis (H1) is accepted, meaning that the Shari'ah compliance variable affects the decision variable to become a member. Keywords: Shari'ah compliance; Sharia Cooperatives; Decision to become a member